YHWH as Caring Eagle: Using Conceptual Metaphor Theory to Explore נשׁר in the Song of Moses - REY, Naomi (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
An eagle exhibits impressive speed and strength as a bird of prey. In the Song of Moses, נשׁר, often translated as ‘eagle,’ is used as an appropriate image to describe YHWH in Deut. 32:11: “As a נשׁר protects its nest, over its young it hovers, he spreads his wings, he takes him, he bears him on his pinions.” Several studies have been concerned mainly with the identity of נשׁר, attempting to locate its place in contemporary scientific taxonomies. However, there has been little discussion about the underlying motivations for using this bird of prey to describe YHWH in the first place. This study explores the use of נשׁר in light of Conceptual Metaphor Theory (CMT). The first portion of the study surveys recent scholarship on Deut. 32:11, while the second explains CMT. The third portion then applies the CMT perspective to the text. Deut. 32:11 puts forward the metaphor YHWH as CARING EAGLE, but there may be an even larger metaphor at play in the ancient Near East: GOD as BIRD.